1982
DOI: 10.1111/j.1469-1809.1982.tb00694.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risks for familial reciprocal translocations with special emphasis on those leading to 9p, 10p and 12p trisomies

Abstract: An analysis of genetic risks for reciprocal translocations is given. Data from translocation families, ascertained through unbalanced offspring with trisomy 9p, 10p and 12p, were taken from the literature. The translocations were specified according to (1) the type of trisomy, (2) the degree of resulting chromosomal imbalance (partial short arm trisomies, complete short arm trisomies, complete short arm trisomies including long arm segments) and (3) the type of disjunction (2:2 or 3:1) and segregation (adjacen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 68 publications
2
30
0
Order By: Relevance
“…[3] This result from the production of gametes and embryos with unbalanced chromosome sets. [45] The clinical consequences of such abnormal gametes include sterility, repeated abortions, and giving birth to malformed children. [67] The majority of chromosome rearrangements are balanced reciprocal and Robertsonian translocations.…”
Section: Introductionmentioning
confidence: 99%
“…[3] This result from the production of gametes and embryos with unbalanced chromosome sets. [45] The clinical consequences of such abnormal gametes include sterility, repeated abortions, and giving birth to malformed children. [67] The majority of chromosome rearrangements are balanced reciprocal and Robertsonian translocations.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] This results from the production of gametes and embryos with unbalanced chromosome sets. 9,10 The clinical consequences of such abnormal gametes include sterility, repeated abortions, and giving birth to malformed children. 11,12 Several studies have been done in various countries to determine the contribution of chromosome abnormalities in parents with fetal wastage.…”
mentioning
confidence: 99%
“…Both modes of unbalance are represented in the present pedigree. The reason for this difference is uncertain, but may in part be related to the fact that the breakpoint in chromosome I 1 in the 11;22 translocation is more proximal than in chromosome 5 in the present case, resulting in a larger chromosomal unbalance in the former (Stene & Stengel-Rutkowski 1982). A further difference between the 11 ;22 translocation and the present 5;22 translocation is the relative low risk for unbalanced offspring of carriers of the 1 1 ; 22 translocation compared to the observed high risk in the present case.…”
Section: Discussionmentioning
confidence: 66%
“…It has been shown that the risk depends on the nature of the involved chromosomes and the position of the breakpoints, which determines the degree of unbalance (Stene & Stengel-Rutkowski 1982). It has been shown that the risk depends on the nature of the involved chromosomes and the position of the breakpoints, which determines the degree of unbalance (Stene & Stengel-Rutkowski 1982).…”
mentioning
confidence: 99%